Kajian Filosofis Hukum Keluarga Islam Sebagai Kewajiban Suami Memberikan Nafkah Istri Dan Anak - Mutamakin, M.; Ansari, Ansari (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2020)
Marriage is a legal act that is binding between a man and a woman (husband and wife) that contains the value of worship. In a marriage there are rights and obligations of husband and wife that one of them is about the living. A living is to meet the needs of the family was born and inner. Meet all the needs of the family. Living well is the cost of living which includes food, pakaiana, facilities and infrastructure needed by the family. Living is not just a gift given to a husband to his wife, but also an obligation between the father with his son and also has the responsibility among an owner with something he had. Maintenance obligation is stipulated in Al-Quran Surat Ath Thalaaq verse seven, surah al Baqarah verse two hundred thirty-three and al Hadith as well as in KHI chapter XII Chapter seventy-nine until the future twenty-four and KHU Civil chapter V, Article one hundred seven Paragraph (2). Living means an obligation that must be dilkasanakan the form of shopping related to basic needs of both husband to wife and father to the child or his family. So the importance of living in the study of Islamic law, even of a wife who is dithalaq by her husband is still entitled to earn a living for herself and her son. In addition, even though a living is an obligation to be fulfilled but it concerns the levels of living, must first see the limits of the ability of the provider.